THE COMMONALITY AND UNIQUENESS OF ARTISTIC PRINCIPLES IN THE WORKS OF WILLIAM SHAKESPEARE AND ALISHER NAVOI - Usmanova Sevara Sultanovna; Ro’ziyeva Nilufar Adkhamjon qizi (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract: This article explores the commonality and uniqueness of artistic principles in the works of William Shakespeare and Alisher Navoi, two literary giants from different cultural backgrounds and time periods. Despite their differences, both writers are celebrated for their mastery of language, exploration of universal themes, and deep understanding of human nature.